An evaluation of the factor that influence users' in Malaysia prefer Low Cost Carriers (LCCS) Services - Cheah, Wai Min; Sabar, Rohafiz (2012)
The research aim to evaluate of the factors that influence users in Malaysia prefer Low Cost Carriers (LCCs) Services. These studies are to determine the relationship between users‟ demography and the factor that may influence users in Malaysia to travel, satisfaction level on the LCCs‟ reliability and responsiveness.The study was conducted by distributing questionnaires to 100 users who come from different background such as occupation, ages and so on. By using descriptive and inferential analysis, the relationships between the independent and dependent variables were identified.